Republic of Slovenia : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2015)
This 2014 Article IV Consultation highlights that Slovenia is recovering from a deep crisis. Growth is estimated to have reached about 2.6 percent in 2014, supported by strong exports and EU-funded public investment. The financial sector has stabilized following recapitalization of the major banks by the state. Government bonds yields have declined markedly. Growth is projected at about 1.9 and 1.7 percent in 2015 and 2016, respectively, with potential growth well below precrisis levels. Executive Directors welcomed the fact that Slovenia's economy is recovering and commended the authorities for their efforts to mend the banking system, facilitate corporate debt restructuring, and consolidate the public finances.